Remote condition monitoring and validation of railway points - Zhou, F; Archer, N; Bowles, J; Duta, M; Henry, M; Tombs, M; Zamora, M; Baker, S; Burton, C (2002)
Remote condition monitoring and validation of railway points were discussed. Recent developments in microelectronics and information technology (IT) made possible low-cost, high-quality condition monitoring for trackside equipment. These equipments reduced the likelihood to breakdown and to enhance railway service quality. The results showed that there was value in continuous monitoring of the overall infrastructure which provided fundamentally new data not available under existing maintenance practice.